A human-specific, truncated α7 nicotinic receptor subunit assembles with full-length α7 and forms functional receptors with different stoichiometries - Lasala, Matías Marcelo (2018)
The cholinergic 7 nicotinic receptor gene, CHRNA7, encodes a subunit that forms the homopentameric 7 receptor, involved in learning and memory. In humans, exons 5–10 in CHRNA7 are duplicated and fused to the FAM7A genetic element, giving rise to the hybrid gene CHRFAM7A. Its product, dup7, is a truncated subunit lacking part of the N-terminal extracellular ligand-binding domain and is associated with neurological disorders, including schizophrenia, and immunomodulation. We combined dup7 expression on mammalian cells with patch clamp recordings to understand its functional role. Transfected cells expressed dup7 protein, but they exhibited neither surface binding of the 7 antagonist -bungaro-toxin nor responses to acetylcholine (ACh) or to an allosteric agonist that binds to the conserved transmembrane region. To determine whether dup7 assembles with 7, we generated receptors comprising 7 and dup7 subunits, one of which was tagged with conductance substitutions that report subunit stoichiometry and monitored ACh-elicited channel openings in the presence of a positive allosteric 7 modulator. We found that 7 and dup7 subunits co-assemble into functional heteromeric receptors, which require at least two 7 subunits for channel opening, and that dup7’s presence in the pentameric arrangement does not affect the duration of the potentiated events compared with that of 7. Using an 7 subunit mutant, we found that activation of (7) 2 (dup7) 3 receptors occurs through ACh binding at the 7/7 interfacial binding site. Our study contributes to the understanding of the modulation of 7 function by the human specific, duplicated subunit, associated with human disorders.